Core Skills in History One - Bateman R.; Gardner P. W; Holmes Mcdougall (1988)
This book offers a balanced coverage of historical periods, covering chosen topics to develop key skills. Introduction, Study Skills, Evidence, Investigating History, History in Britain, World History, Conflict in History, History from Below, Study Trough Time, Chronological Scales, Acknowledgements.